STUDY ON THE ENVIRONMENTAL ASPECTS OF PIT CLOSURE GUIDELINES FOR OIL AND GAS PRODUCTION ACTIVITIES - M. Mulyono (Scientific Contributions Oil and Gas, 2006)
Exploration, development, and production activities associated with oil and gas production projects can have a variety of impacts on the environment. A variety of wastes are produced by such activities. Apart from the wastewater that is in the form of produced water, many kinds of solid wastes are produced during exploration and production of oil and gas. These solid wastes, among others, are drilling mud and cuttings, and tank bottom oily sludge. These solid wastes are dumped temporarily in a certain place called a pit before they can be treated further. In order to minimize and possibly eliminate the environmental impacts of those solid wastes, pit construction has to be developed in such a way that release of pit contents to the environment could be prevented. In addition, pollutant loading of ground water from waste leaks, releases of hydrocarbons and hydrogen sulphide to the atmosphere are some of the factors that have also to be considered. As dumping such solid wastes in a pit is a temporary storage, pit closure management has also to be developed. Explicitly, governmental regulation concerning with environmental aspects of pit closure has not been established yet. Nevertheless, environmental management approach of pit construction and closure could be established by referring to the available regulation, namely Governmental Regulation PP. 18/1999 juncto PP. 85/1999 - hazardous waste regulation, and the related Ministerial Decree, such as Bapedal Decree No. Kep.-04/BAPEDAL/09/19995 decsribing methods of landfilling or land disposal for hazardous wastes. This approach is based on the reason that such solid wastes are also categorized as hazardous wastes. In regard to pit construction, study on pit location should include the hydrogeology pattern of the site. Furthermore, pit wall materials are parameters that also have to be considered in minimizing impacts to the surrounding. Upon closing the pit, a pit closure plans that call for the dewatering of mud and reserve pit contents before burial have to be developed to reduce the chance of the downward transport of contaminants to shallow aquifers. The grading of soils covering the pits may reduce the chances of infiltration of rainwater, which may migrate to ground water. Other consideration, for example revegetation, has also to be included. All of the above factors should be considered in pit closure and assessment guideline. In addition to the available national references, other worldwide references such as those of US-EPA guidelines deserve to be considered in studying pit management. The author has conducted a short study concerning pit closure management that has been implemented in oil and gas producing companies. Goals of the study are to review the manual guideline or standard operating procedure (SOP) of pit closure applied to the fields. The followings are report concerning with the implementation of the study.